Scaling up HIV/AIDS interventions through expanded partnerships (STEPs) in Malawi - Kadiyala, Suneetha (International Food Policy Research Institute, 2004)
This paper discusses enabling and constraining factors related to the scaling-up of the Scaling Up HIV/AIDS Interventions Through Expanded Partnerships (STEPs) initiative, supported by Save the Children U.S.A. (SC), to combat HIV/AIDS in Malawi. It also discusses potential threats to and contextual factors limiting scaling up of STEPs. The report draws primarily upon the available literature and qualitative data collected during a five-day visit to SC Malawi in December 2002. STEPs started in 1995 as Community-Based Options for Protection and Empowerment (COPE). COPE was a service-delivery program in Mangochi District to assist children affected by HIV/AIDS. Through evaluations, SC realized that such an approach was unsustainable, not cost-effective, and not scalable. Based on the recommendations of the evaluations and on field experience, the program changed course to mobilize collective action to combat the epidemic. Working in the Namwera community in Mangochi under the National AIDS Commission (NAC), STEPs revitalized the dormant decentralized AIDS committees and their technical subcommittees at the district, community, and village levels. Based on the positive experience in Namwera, the program changed its initial strategy to that of an external change agent, assisting communities with community mobilization and capacity building so that communities became empowered to act collectively to address their problems. Village AIDS committees (VACs) first identify the vulnerable. Then VACs plan responses on the basis of the nature and magnitude of vulnerability within the villages, needs of the vulnerable, and capacity within villages to respond. The committees also monitor activities and mobilize resources. As the needs of the most affected communities are crosscutting, the program has become truly multisectoral, with activities along the continuum of prevention, care, support, and mitigation. STEPs has also been influencing national policies related to HIV/AIDS and children.